Agro-morphological diversity of some accessions of bread wheat (Triticuma estivum) in western Algeria - AMINA BELLATRECHE; MOUSTAFA YASSINE MAHDAD; ZOUBEYDA KAHOUADJI; SEMIR BECHIR SUHEIL GAOUAR (Society for Indonesian Biodiversity, 2017)
Abstract. Bellatreche A, Mahdad MY, Kaouadji Z, Gaouar SBS. 2017. Agro-morphological diversity of some accessions of breadwheat (Triticum aestivum) in western Algeria. Biodiversitas 18: 409-415. The diversity of wheat in Algeria is well known. An inventory has been conducted in the west of Algeria (North and South) to collect local accessions of bread wheat Triticuma aestivum for their morphological characterization. In this context, a collection of 23 traditional and new accessions of bread wheat was investigated using nine quantitative agro-morphological traits. The phenotypic diversity was determined by the Shannon-Weaver diversity index (H') at different levels (sample Totality which is by type of wheat and varietal name). The H' showed a wide phenotypic variability for different traits with H’ average of 0.59. The results of the multiple correspondence analysis and hierarchical clustering showed a clear distinction between different accessions. The results of this work have revealed the great phenotypic diversity of wheat accessions. These accessions were partially matched the names of varieties because of the existence of homonyms and synonyms in the names given by farmers. The results showed that these local accessions (that genetic composition should be studied more precisely) are mainly cultivated by traditional farmers who conserve this genetic resource, often on very small plots in the oases or in an inaccessible terrains. Keywords: Algeria, morphological diversity, morphological traits, Triticuma aestivum